Hubungan anatara Manajemen Diri dan Interaksi Siswa-Guru dengan Disiplin Belajar - Alfarabi, Mr. Abdurrahman; , Dr. Yadi Purwanto, M.M (2015)
The aims of this research are to determine: 1) A relationship between self management and student-teacher interaction with learn-discipline; 2) A relationship between self management with learn-discipline; 3) A relationship between student-teacher interaction with learn-discipline. The subjects of this research are students from SMKwith the number of students are 91 students. The data collection method used self management scale, student-teacher interaction scale and learn-discipline scale. The method of analysis data used multiple regression analysis and stepwise regression. The result of data analysis suggests that there is a significant relationship between self management and student-teacher interaction with learn-discipline, there is a significant relationship between self managementwith learn-discipline and there is a significant relationship between student-teacher interaction with learn-discipline. The aspect of self management variable that has the most dominant influence is time management, while aspect that has the smallest influence is self control and management. As for aspect of student-teacher interaction variable that has the most dominant influence toward learn-discipline is empathy, while the smallest influence and insignificant is extrovert behavior aspect.